The Implementation of The Jakarta Smart City (JSC) Evi Satispi and Kurniasih Mufidayati - Evi Satispi; Kurniasih Mufidayati (Iapa Proceedings Conference, 2018)
Jakarta wants to be an informative, transparent, and high technology city. The Jakarta Smart City (JSC) policy has been implemented since 2014, developing and improving public services in terms of information services more easily and better for citizen. At least there are eight applications that have already supported the implementation of JSC, such as the Qlue and Zomato JSC. Now, Implementation of the JSC in the state capital, Jakarta, still finds a number of challenges. Jakarta has not succeeded yet , getting the Indonesian Smart City Rating (RKCI) at the end of 2017. The problem of this research is to answer "How is Jakarta Smart City (JSC) Policy Implementation in Jakarta?" This study uses a qualitative approach and descriptive method. A number of JSC stakeholders were interviewed in depth as informants, both from JSC managers and the community as users. The study was conducted on a number of Smart City applications in Jakarta and Surabaa. The theories of Colldahl (2013) and Griffinger (2007) about Smart City used as the foundations and theory framework of this research. This concept explained the Six Smart City Characteritics for analyze the JSC implementation in Jakarta. The results of this research showed that Jakarta, respectively, already have many programs and applications for the those Six characteristics of Smart City. Jakarta has just implemented smart city in 2014. Jakarta has succeeded getting Smart City awards from many institutions and foundations.